PERAN KEGIATAN UNHAN MENGAJAR DALAM MENANAMKAN SIKAP BELA NEGARA PADA SISWA-SISWI SMAN 67 JAKARTA - Gathut Imam Gunadi; Waskito Dwiwicaksoputro; George Royke Deksino (IKIP PGRI PONTIANAK, 2023)
State defense, especially the Unitary State of the Republic of Indonesia, which is based on the philosophy of Pancasila and the 1945 Constitution, is the determination, attitude, and behavior of citizens, both individually and collectively, to uphold a state sovereignty, as well as territorial integrity, as well as for the safety of the nation and state. This study tries to explain how the activities of the Defense University help students at SMAN 67 Jakarta adopt a State Defense mentality. To provide descriptive data, the research methodology combines a literature study approach with a qualitative methodology. The conclusion of this study emphasizes the importance of instilling the attitude of Defending the State in the younger generation including a sense of love for the homeland, knowledge of the state and nation, acceptance of Pancasila as the official state ideology, willingness to sacrifice individual and group interests for the state and nation, and initial ability to defend the state.